Microcontroller based head-lamp alignment system for automobile - Leong, Zi Zheng (2016)
This thesis deals with microcontroller based head-lamp alignment system for auto mobile. The objective of this thesis is to design a headlamp system for automobile that can turn angle of headlamp to have a better vision. A driver drives a car on road when goes to sharp corner at night that will some area that the light of headlamp cannot reach. Sometime driver may forget turns off the high beam and cause the other driver uncomfortable and cannot see the front view from opposite lane. Therefore, the design of headlamp alignment system is important to solve this issue. The other objective is to fabricate a headlamp model that can be control with Arduino Mega. Also make a choosing mode for driver to choose auto mode or manual mode operation. In auto mode operation, all input device is use sensor such as ultrasonic and potentiometer to control the alignment system of headlamp; all are automatically control the alignment system without used any switch. While in manual mode operation, all are using toggle switch to control the headlamp alignment system and need to turns on the switch manually.